Nursing Modality Therapy (Spiritual Deep Breathing) Resolve Student Distress - Kushariyadi Kushariyadi; Grysha Viofananda Kharsima Ade Agung; Faizatul Mazuin; Fitriany Fitriany (Faculty of Nursing Universitas Padjadjaran, 2019)
The condition of nursing faculty students has many academic tasks such as attending classes, taking exams, socializing, adjusting to fellow students with different characteristics and backgrounds, developing talents and interests through non-academic activities. This condition causes students to not be able to manage time well so that they experience distress. Quasy experiment research used two groups pre-post-test design. The sample included 15 control groups and 15 treatment groups. The sampling technique uses simple random sampling. Research variables include spiritual deep breathing therapy and distress rate. The instrument uses depression anxiety stress scale-42 (DASS-42) in the form of a Likert scale. This type of unfavorable questionnaire contains 42 questions. The spiritual instrument deep breathing therapy is about 20 minutes a day for seven days. Statistical test using Wilcoxon signed rank test against both groups. There was a significant effect on the treatment group (p-value 0.001). In the control group there was no effect (p-value 0.263). Distress conditions in a person can be overcome with one therapy such as spiritual deep breathing therapy. Spiritual deep breathing therapy as a therapy for nursing modalities can optimize oxygen demand for cells that are distressed, blood flow to the muscles decreases otherwise blood flows to the brain and skin increases so as to provide a sense of warmth, comfort and calm.